2015
DOI: 10.1016/j.jallcom.2014.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cold Gas Spray process conditions on the microstructure of Fe-based amorphous coatings

Abstract: a b s t r a c tFe-based amorphous metallic coatings were prepared by Cold Gas Spray process. Through this study, the effects of the process conditions such as spraying distance, gas pressure and temperature on the microstructure of as-sprayed coatings are evaluated. Microstructural studies show that the coatings can present a densely layered structure with porosity below 0.5% and thickness around 800 lm depending on the process conditions. Precipitation of nanocrystals in as-sprayed coatings is observed and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 31 publications
(45 reference statements)
2
31
0
Order By: Relevance
“…The obtained coatings exhibited tribological and corrosive properties similar to that of cast BMG [208][209][210]. More recent studies demonstrated that amorphous coatings of Fe-based BMGs could be deposited by using nitrogen as process gas [87,88,96,211]. Figure 28.…”
Section: Metallic Materialsmentioning
confidence: 82%
See 1 more Smart Citation
“…The obtained coatings exhibited tribological and corrosive properties similar to that of cast BMG [208][209][210]. More recent studies demonstrated that amorphous coatings of Fe-based BMGs could be deposited by using nitrogen as process gas [87,88,96,211]. Figure 28.…”
Section: Metallic Materialsmentioning
confidence: 82%
“…A presumption is that the particle temperature should be above Tg, allowing for viscous flow of the material in the undercooled liquid state [86]. Recent investigations on Fe73Cr2Si11B11C3 attributes successful deposition to viscous flow at high (> 10 -3 ) Reynolds numbers [87,88]. This interpretation cannot explain experiments using helium as process gas, where particles cool down to temperatures below Tg.…”
Section: Bonding Of Brittle Materialsmentioning
confidence: 99%
“…These equations are solved by substituting the boundary conditions in Table 1. The exit velocity was calculated from Equation (20). Table 1.…”
Section: » --mentioning
confidence: 99%
“…Bulk MGs are manufactured by different techniques, all including a rapid quenching step, yielding materials characterized by a short-range order but typically endowed with very limited ductility and with negligible plastic behavior in compression [9]. For these reasons, commercial applications of this class of materials are not yet consolidated.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal-sprayed coatings of amorphous metals represent a viable alternative solution to producing MGs, while preserving their exceptional properties and avoiding extreme brittleness [9]. In fact, the lack of grain boundaries, representing the weak points of crystalline materials, can be responsible for improved resistance to wear and corrosion [10], and these protection properties can be easily conferred by surface layers deposited on tough and plastically deformable structural substrates.…”
Section: Introductionmentioning
confidence: 99%